2022
DOI: 10.1111/risa.13935
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of banknotes as a fomite of SARS‐CoV‐2 in cash payment transactions

Abstract: The COVID 19 pandemic has triggered concerns and assumptions globally about transmission of the SARS‐CoV‐2 virus via cash transactions. This paper assesses the risk of contracting COVID‐19 through exposure to SARS‐CoV‐2 via cash acting as a fomite in payment transactions. A quantitative microbial risk assessment was conducted for a scenario assuming an infectious person at the onset of symptoms, when virion concentrations in coughed droplets are at their highest. This person then contaminates a banknote by cou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…As the World Health Organisation (WHO) and studies Tang et al (2020) highlight, transmission is possible via direct and indirect contacts, increasing the infection risk. The rise of concerns about cash contamination has widely contributed to the alertness and reluctance to use cash for financial transactions (Schijven et al, 2022). Accordingly, banks, consumers, and governments sought safer alternatives, favouring digital modes wherever possible.…”
Section: Research Frameworkmentioning
confidence: 99%
“…As the World Health Organisation (WHO) and studies Tang et al (2020) highlight, transmission is possible via direct and indirect contacts, increasing the infection risk. The rise of concerns about cash contamination has widely contributed to the alertness and reluctance to use cash for financial transactions (Schijven et al, 2022). Accordingly, banks, consumers, and governments sought safer alternatives, favouring digital modes wherever possible.…”
Section: Research Frameworkmentioning
confidence: 99%
“…Of these, only Omicron remains in circulation and has already produced nearly one thousand sub-lineages or subvariants. These mutating variants demonstrate increased infectivity and vaccine breakthrough rates, as well as more pronounced antibody escape rates (3).…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 is primarily a respiratory illness, with its main transmission routes being direct contact and the spread of droplets or aerosols ( 4 ). The Food and Agriculture Organization of the United Nations (FAO) has reported that the likelihood of SARS-CoV-2 transmission via food or food packaging is low, as the virus cannot multiply on such surfaces.…”
Section: Introductionmentioning
confidence: 99%